Language diversity of the Japanese Archipelago and its relationship with human DNA diversity - Naruya, Saitou; Timothy Adrian, Jinam (Serials Publications Pvt. Ltd, 2017)
The Japanese Archipelago stretches over 4000 km from north to south, and is the homeland of three human populations; Ainus, Mainlanders, and Okinawans. The origins of these people have been studied for a long time. The standard theory based on craniofacial data is the "dual structure model" propagated by Japanese physical anthropologists, notably Hanihara (1991). According to this model, first migrants to the Japanese Archipelago came from somewhere in Southeast Asia in Upper Paleolithic age more than 30,000 years ago, and were probably ancestors of the Jomon people. The second wave of migration is believed to have taken place later in the Yayoi period (3000-1700 BP), where the people arrived from Northeast Asia. Indigenous Jomon people and new migrants in and after Yayoi period gradually mixed with each other. This model provides a reasonable explanation for the morphological similarity between the Ainu people of Hokkaido at the northernmost main island of Japanese Archipelago, and the Okinawan people in Southwest Archipelago, despite of large geographical distance. Similarity of these peoples was already noticed more than one hundred years ago by von Baelz (1911) who proposed the Ainu-Okinawan common origin theory.